Ekstremisme Game Daring, Protes Roblox, dan Konsep Hyperreality Demonstrasi Agustus di Indonesia Dalam Politik Postmodern - Nadhira Shania Tabrizia Azis; Chanifia Izza Milata (PERSPEKTIF, 2026)
This article aims to examine the phenomenon of digital demonstrations on the Roblox platform in August 2025 as a form of postmodern political representation within the dynamics of Indonesia’s digital democracy. In this context, the focus is on how virtual protest practices shape politically mediated discourse through technology and how the boundary between political reality and simulation becomes increasingly blurred. This article employs Jean Baudrillard’s theory of hyperreality, the concept of gamification in digital activism, and Norman Fairclough’s critical discourse analysis as its analytical framework. The study finds that digital demonstrations on Roblox not only function as an alternative space of expression with the potential to expand democratic practices but also reveal that political action conducted through Roblox no longer emphasizes grassroots ideological grounding, instead prioritizing visibility, accessibility, and popularity. Rather than merely extending social media–based political mobilization, the use of Roblox ultimately facilitates capitalist practices that benefit corporate actors and operate through algorithmic agents. This phenomenon indicates that such digital protests tend to neglect ethical dimensions and ideological grounding, focusing instead on aesthetics and the imperatives of participation in the digital era.